The Relationship Between the Leadership Behaviors of Administrators in Preschool Education Institutions and Teacher Identification - Polat, Sinan; Polat, Sevda Müge; Özdemir, Tuncay Yavuz (Yildiz Technical University, 2025)
This study examined the impact of the leadership behaviors of school principals working in preschool education institutions in Elazığ on teachers' organizational identification. Since the Industrial Revolution, the concept of leadership has been seen as an important factor in performance evaluation and organizational development. School leadership plays a critical role, particularly in the identification of teachers, and this study evaluates the relationship between leadership behaviors and teachers' perceptions of identification. The study was conducted in independent kindergartens in Elazığ province, with the participation of 199 preschool teachers. The data collection tools used in the research were the Multiple Organizational Identification Scale and the Leadership Behavior Inventory. The findings indicated that the leadership behaviors of school administrators affected teachers' levels of identification, and this effect varied depending on the leadership style. This study will contribute to the development of school administrators' leadership styles and to support the identification processes of teachers, thereby increasing the efficiency of the education system.

Bu araştırma, Elazığ ilindeki okulöncesi eğitim kurumlarında görev yapan okul müdürlerinin liderlik davranışlarının öğretmenlerin örgütsel kimliklenmeleri üzerindeki etkisini incelemektedir. Sanayi devriminden itibaren liderlik kavramı, performans değerlendirme ve örgütsel gelişimde önemli bir faktör olarak görülmüştür. Okul liderliği, özellikle öğretmenlerin kimliklenmelerinde kritik bir rol oynar ve bu araştırma, liderlik davranışları ile öğretmenlerin kimliklenme algıları arasındaki ilişkiyi değerlendirmektedir. Araştırma, Elazığ ilindeki bağımsız anaokullarında yürütülmüş olup, 199 okul öncesi öğretmeninin katılımıyla gerçekleştirilmiştir. Araştırmada veri toplama aracı olarak Çoklu Örgütsel Kimliklenme Ölçeği ve Liderlik Davranışı Envanteri kullanılmıştır. Araştırma sonuçları, okul yöneticilerinin liderlik davranışlarının öğretmenlerin kimliklenme düzeylerini etkilediğini ve bu etkinin, liderlik tarzına bağlı olarak farklılaştığını göstermektedir. Bu çalışma, okul yöneticilerinin liderlik stillerini geliştirmelerine ve öğretmenlerin kimliklenme süreçlerini desteklemelerine katkı sağlayarak, eğitim sisteminin verimliliğini artırmayı amaçlamaktadır.
Okulöncesi Eğitim Kurumlarındaki Yöneticilerin Lider Davranışlarının Öğretmen Kimliklenmeleri ile İlişkisi
Keywords: Classroom Education; Sınıf Eğitimi